A 3D computational model of electrospun networks and its application to inform a reduced modelling approach. (February 2019) - Domaschke, Sebastian; Zündel, Manuel; Mazza, Edoardo; Ehret, Alexander E.
Abstract: In this contribution, a full 3D finite element model of electrospun networks is presented. The model explicitly accounts for the specific microstructure of these networks by generating representative volume elements through a particular fibre deposition method inspired by the process of network formation during electrospinning. The modelled fibre material and structural properties, such as different fibre shapes and distributions in diameter, can vary over a wide range, and mutual fibre contact is considered in addition to permanent cross-links. In addition to the homogenized mechanical response to macroscopic in-plane loads, the model provides access to structural information which can hardly be determined in experiments, such as fibre disposition and interconnectivity. In the present work, this asset is used to inform a recent 2.5D modelling approach (Zündel et al., 2017) and to validate inherent assumptions on network structure. The comparison between the responses of the two approaches reveals that for networks of high porosity, the reduced 2.5D model captures well the mechanical behaviour in plane stress load cases. At lower porosities though, the increasing out-of-plane orientation of fibre segments leads to effects that cannot be captured by planar approaches and necessitate a 3D approach.